The next steps - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
CTA seminar 2000, held in Paris from 29 May to 2 June 2000, had as its theme 'information for agricultural and rural development in ACP countries: new stakeholders, new media and priority themes'.